AGE IN BOXERS SPEED-STRENGTH ADJECTIVES AND OPTIMAL METHODS FOR PARALLEL DEVELOPMENT OF ENDURANCE . - Ibragimov Mironshokh Mukhammedovich (International Journal of Literature and Language Studies, 2026)
This article explores the optimal methods for the parallel (concurrent) development of speed-power qualities and endurance in the physical training process of young boxers. The high dynamics of combat in modern boxing require athletes to possess both high speed and explosive power, as well as specific endurance to maintain this tempo throughout all rounds. The paper analyzes interval and circuit training methods, block periodization, and the volume of specific workloads that enable the balanced development of these two contrasting functional qualities within a single training system. The results of the study serve as methodological recommendations for enhancing the functional capacity of young boxers and designing training process efficiency.